Association of fasting blood glucose with non alcoholic fatty liver in type 2 diabetes mellitus patients (Journal of Dhaka National Medical College & Hospital, 2013)
Type 2 diabetes mellitus (T2DM) and metabolic syndrome are the risk factors for non-alcoholic fatty liver disease (NAFLD). Insulin resistance might have a role in disease progression. The present study was under taken to find out any association between fasting blood glucose and NAFLD in Bangladeshi population. 256 T2DM subjects were included in this study. Out of them 127 subjects of NAFLD were taken as case and rest 129 without fatty liver were taken as control. Anthropometric measurements, fasting blood glucose, SGPT, lipid profile were estimated. Data was analyzed by appropriate univariate and multivariate statistical tools. Mean (±SD) of age of case and control were 43.33±6.36 and 42.89±5.85 years, mean (±SD) of BMI of case and control were 26.19±3.69 and 25.32±3.47, mean (±SD) of waist hip (WH) ratio between case and control were 0.923±0.06 and 0.918±0.074 respectively and statistically no significant difference was found between the two groups. Median (range) value of fasting blood glucose between case and control were 6.70 (3.60-23.0) and 5.10 (4.0-5.9) mmol/L respectively and statistically no significant difference was also found. Median (range) value of SGPT of case and control were 36 (10-150) and 23(10-324) U/L respectively. This result only showed statistically significant difference. Multiple regression analysis taking the fatty liver as dependent variables and age, WH ratio, BMI, SGPT, FBG as independent variables, a positive significant association was found with SGPT but FBG did not show any significant association with NAFLD. From this study it is suggested that there is no association between hyperglycemia and NAFLD in Bangladeshi T2DM subjects.J. Dhaka National Med. Coll. Hos. 2013; 19 (02): 28-31